Putting political spectacle to work: Understanding local resistance to the Common Core - Michael A. Szolowicz (Arizona State University, 2016)
In the fall of 2013, a parents' group formed to protest the new Common Core based mathematics textbook recently adopted by their school district. Quickly allying with teachers, the new coalition began to, "hammer," the district to drop the Common Core and return to more traditional texts and pedagogies. They did so by speaking at Governing Board meetings, participating in interviews with local newspapers, appearing on a local radio talk show, and forming social media accounts. This intrinsically motivated case study uses qualitative media analysis to examine the texts produced from these and other public declarations to better understand local policy formation through the mechanics of "political spectacle."  Political spectacle theory suggests that policy may be formed through dramatic public displays and that policy formed from such spectacles often undemocratically reinforces existing inequalities. The study analyzes the parent, teacher and administration policy actors' use of political spectacle elements such as symbolic language, construction of problems, casting of enemies and allies and distinctions between onstage and backstage drama to understand the adoption, challenge and ultimate rejection of a Common Core based mathematics text in a mid-sized southwestern United States School district.